Damage to the insula leads to decreased nicotine withdrawal during abstinence. (8th September 2015) - Abdolahi, Amir; Williams, Geoffrey C.; Benesch, Curtis G.; Wang, Henry Z.; Spitzer, Eric M.; Scott, Bryan E.; Block, Robert C.; van Wijngaarden, Edwin
Abstract: Background and Aims: Current pharmacotherapies for tobacco dependence are generally well tolerated, but have relatively high rates of relapse. They target primarily the brains' mesocorticolimbic 'reward' pathway. However, recent evidence suggests that the insular cortex, a central cerebral hemispheric region historically overlooked in addiction models, may also play an important role in cognitive and emotional processes that facilitate drug use. We examined whether insular versus non‐insular damage from ischemic stroke attenuated acute withdrawal from cigarette smoking and reduced the likelihood of nicotine replacement therapy (NRT) use during hospitalization. Design: Data were derived from a longitudinal study with 3 months' follow‐up, beginning June 2013 and ending May 2014. Setting: Three acute care hospitals in Rochester, NY, USA. Participants: One‐hundred and fifty‐six current smokers hospitalized for acute ischemic stroke (38 with insular infarctions and 118 with non‐insular infarctions, assessed by three neuroradiologists). Measurements: The Wisconsin Smoking Withdrawal Scale (WSWS) and Minnesota Nicotine Withdrawal Scale (MNWS) were administered during hospitalization (a period of forced abstinence) to assess the frequency and severity of withdrawal symptoms. NRT use was also assessed during hospitalization. Findings: On average, smokers with insular damage had a lower WSWS score during admission [mean = 5.89, standard deviation (SD) = 4.72] compared with those with non‐insular damage (mean = 9.20, SD = 4.71; P < 0.001) [covariate‐adjusted difference in means of –3.12, 95% confidence interval (CI) = –4.97, –1.27]. A similar difference was also noted when the MNWS was used ( P = 0.02). Furthermore, participants with insular lesions appeared to be less likely to use NRT during admission compared with those with non‐insular lesions [odds ratio (OR) = 0.72, 95% CI = 0.32, 1.64]. Conclusions: Current smokers with damage to their insular cortex brain region appear to experience fewer and less severe tobacco withdrawal symptoms, and appear to be less likely to require nicotine replacement therapy during hospitalization, compared with smokers with non‐insular damage. These findings support the potential role of the insular cortex in regulating withdrawal during abstinence, a motivator responsible for the maintenance of addictive behaviors.